Salmonella LVR01 triggers antagonistic two-armed innate immune memory that impacts on antitumor efficacy - Chilibroste, Sofía; dos Santos, Jéssica C.; Mónaco, Amy; Joosten, Leo A. B.; Moreno, María; Chabalgoity, José A. (Frontiers in Immunology, 2025)
The current understanding of innate immune memory encompasses both trained immunity and immune tolerance, where cells can exhibit enhanced responsiveness or immune paralysis upon subsequent stimuli, respectively. Various agents induce either of these responses, including β-glucan, Leishmania, BCG and LPS. BCG is a clinically approved immunotherapy for bladder cancer and BCG-induced trained immunity is important in driving anti-tumor adaptive immunity. Salmonella also shows promise in cancer treatment, eliciting potent anti-tumor immune responses, but with transitory effects. This led us to investigate whether Salmonella LVR01, like BCG, triggers trained immunity and its impact on anti-tumor responses. Herein, we report that Salmonella induces an enhanced response in bone marrow cells, characterized by a robust cytokine response upon a second stimulus, in a fashion that resembles trained immunity. Coherently with that, Salmonella administration induces enhanced responsiveness to a tumor implanted later in time, resulting in slow tumor growth and extended survival. However, in vitro stimulation of human monocytes and murine bone-marrow derived myeloid-enriched cells with Salmonella results in decreased production of cytokines resembling immune paralysis. Overall, our results suggest that Salmonella LVR01 induces enhanced responses of innate immune memory, as well as paralysis on monocytes. These two antagonistic effects could be the basis of the transitory effect of Salmonella treatment and suggest that further investigation on these phenomena could shed light on how to improve Salmonella-based immunotherapies for cancer.